ENVIRONMENTAL ASSESSMENT OF SUBURBAN AREAS OF KYIV - Кіchata, Natalia; Zaplatynskyi, Vasyl (Proceedings of National Aviation University, 2014)
Nowadays the investigation of ecological state of suburban areas in Ukraine is one of the leading problems. The suburban areas of Kyiv, environmental problems and their causes are described. Some ways and measures for improvement of environmental situation in the suburbs of Kyiv were revealed. The conclusion of the importance of suburban areas for city life activity was made and the urgent necessity for further all-round investigation of ecological issues of suburban area was shown